Ozone therapy in the treatment of an infected wound in a child in a Public Hospital in São Luís – Maranhão – Brazil. Case report (Ozone Therapy Global Journal, 2020)
Ozone therapy, due to its bactericidal, fungicidal, anti-inflammatory, analgesic and tissue-regenerating properties, has been widely used as a supplement in the treatment of wounds. The objective of this case report is to demonstrate the effectiveness of ozone therapy in the treatment of a 2-year-old and 11-month-old boy admitted to a Public Hospital of Urgency and Emergency, with a large wound on his right foot, infected, with a tibia and fibula fracture, caused by a car accident, that had an adverse reaction to the antibiotic clindamycin and had ozone therapy as the main therapy. The patient was successfully treated with ozone therapy locally (ozonated saline, ozonated bag, and ozonated sunflower oil). The treatment lasted 38 days with a total of 19 ozone therapy sessions. This study adds e.vidence of the usefulness of ozone therapy as an effective and safe method of treating wounds